Nitrogen, Phosphorus and Sulfur Stocks in Soils under Different Land Use Systems at the University of Benin Nigeria. - Emomu, Adams; Aigbobo, Eseuwa Naomi; Olukini, Bisola Elizabeth (Jurnal Ilmu Pertanian, 2025)
Understanding how land use and soil depth influence nutrient storage is essential for sustainable soil management in tropical ecosystems. This study quantified nitrogen (N), phosphorus (P), and sulfur (S) stocks in soils under four contrasting land-use systems—arable, forested, sport, and plantain fields—within the University of Benin, Nigeria. Soil samples were collected at 0–30 cm and 30–60 cm depths and analyzed using standard laboratory methods. Nutrient stocks were calculated based on soil nutrient concentration, bulk density, and depth increments. Land use and soil depth significantly affected N and P stocks, while S stock variation at the surface layer was not significant. At 0–30 cm, the highest N stock (2,360 Mg ha⁻¹) occurred in arable land, likely due to continuous inorganic N fertilizer use, whereas plantain fields stored the highest P (2,354 Mg ha⁻¹) and S (164 Mg ha⁻¹), reflecting greater organic inputs and improved soil chemical properties. At 30–60 cm, N stock peaked in sport land (3,890 Mg ha⁻¹), possibly due to turfgrass management and regular biomass return, whereas forested land stored the most sulfur (433 Mg ha⁻¹), attributed to litter accumulation and microbial activity. Differences in nutrient stocks across land uses corresponded closely to variations in soil organic carbon, pH, and cation exchange capacity. These findings highlight strong land use–driven redistribution of essential nutrients in tropical Ultisols. Promoting land-use practices that enhance organic matter input—such as agroforestry, mixed cropping, or managed fallows—can improve nutrient storage, support long-term soil fertility, and strengthen nutrient cycling in degraded tropical landscapes.